A review of migraine treatment methods: a comparative analysis of therapeutic approaches - Paweł Nojek; Wiktoria Pawlik; Mariusz Zimonczyk; Monika Zawół; Gustaw Błaszczyński; Agnieszka Nowotarska (Journal of Education, Health and Sport)
Migraine, a complex neurological disorder, affects a significant portion of the population and presents both medical and societal challenges. The aim of this paper is to provide a detailed review and analysis of available therapeutic methods for patients suffering from migraines, considering both pharmacological and non-pharmacological therapies. The approaches presented include acute treatment with triptans and nonsteroidal anti-inflammatory drugs (NSAIDs), as well as preventive therapies, such as beta-blockers and antiepileptic drugs. The section on non-pharmacological therapies focuses on cognitive-behavioral therapy (CBT), biofeedback, and lifestyle recommendations, including diet and sleep hygiene. A review of the literature indicates that integrating pharmacological and non-pharmacological approaches can significantly improve treatment effectiveness and the quality of life for patients with migraines.